Is it possible to distinguish the understanding of denture adhesive between Japanese dental students and Indonesian peers by a questionnaire? - Shinsuke Sadamori; Taizo Hamada; Guang Hong; Makoto Kawamura; Nobuyuki Nakai; Arifzan Razak (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
The purpose of this study was to compare cross-national differences in the recognition of denture adhesive between dental students. The design of the research was cross-cultural differences. The research was done in Japan and Indonesia. Seventy-seven dental students from Japan and Indonesia were surveyed using a questionnaire regarding knowledge/comprehension of denture adhesive (in Japanese and Indonesian versions respectively). Logistic regression using the Wald method showed that it was possible to distinguish Japanese dental students from Indonesian peers with a probability of 96.1 per cent by using 3 items out of 12. For the question of “How many domestic products denture adhesive do you know?” 85 per cent of the Japanese dentists answered “less than 3”, whereas 10 percent of Indonesian subjects did so. It was concluded that there were big differences between Japanese and Indonesian dental students’ understanding and experience of denture adhesive.